Hadrontherapy for intra- or para-cardiac tumors: evaluation of cardiac radiation dose distribution and acute cardiac effects. (14th October 2021) - Dusi, V; Barcellini, A; Greco, A; Vitolo, V; Vai, A; Mirandola, A; Zambrino, D; Roccio, M; Coccia, M; Turco, A; Sanzo, A; Vicentini, A; et al.
Abstract: Background: There is growing interest in the possibility of using X-rays and hadrons (protons and carbon ions) for antiarrhythmic purposes both at the ventricular and the atrial level, but knowledge about the effects on cardiac tissue outside the target is still limited. Hadron therapy has the dosimetric advantage over photons of a greater ability to concentrate high doses on the target while minimizing the off-target dose. Oncological studies have shown a linear relationship between the mean total heart dose (Dm-heart) of X-rays and the long-term risk of heart damage, particularly when the Dm-heart is>5 Gray (Gy). Objectives: We designed a prospective study aimed at investigating the effect of heavy particles on cardiac structure and function and on cardiac rhythm in patients undergoing hadrontherapy for intra or para-cardiac tumors. Methods: Patients candidates to hadrontherapy with a mean predicted cardiac dose grather than zero underwent close cardiological monitoring including blood pressure detection, 12-lead ECG, 12-lead Holter ECG (including time-domain indices of heart rate variability in all cases and Brugada leads in selected cases), cardiac US and cardiac (troponin and natriuretic peptides) and inflammatory biomarkers. These assessments were obtained at baseline, during (ECG and biomarkers only) and at the end of the hadrontherapy cycle, and then every 3–6 months as appropriate. Physicists and radiotherapists collaborated to implement a robust optimization of the treatment plan aimed at minimizing cardiac dose. We present the results of the monitoring up to the end of the hadrontherapy. Results: 17 consecutive patients (56±18 years, range 20–77 years, 59% male) have been enrolled to date, including 3 cases (18%) of intra-cardiac tumors (2 primary and 1 metastatic), who have undergone to 16±6 sessions of radiotherapy each, in 71% of cases with respiratory gating during delivery. Most patients (76%) were treated with carbon ions, the remaining with protons (mean total dose on the neoplastic target 51.8±10.7 Gy, from 2 to 4.2 Gy per fraction). Sixty-one percent of patients had ≥1 cardiovascular risk factor, 6% had a known heart disease (valvular cardiomyopathy despite aortic valve replacement with biological prosthesis and post-surgical pericarditis). The mean dose on the whole heart was 3.58±2.05 Gy, the maximum dose was 33.78±23.99 Gy, with a very variable dose distribution on cardiac substructures depending on the tumor site (table). At the end of the scheduled radiotherapy sessions (24±9 days), no significant changes were observed in cardiac function, cardiac rhythm, ventricular repolarization, biomarkers and autonomic indices. Conclusions: Hadrontherapy with protons and carbon ions aimed at the treatment of para-cardiac or intra-cardiac tumors allowed to maintain a low heart Dm and showed no signs of acute cardiac toxicity. The collection of potential cardiac effects in the medium and long term is ongoing. Funding Acknowledgement: Type of funding sources: None.